2024
DOI: 10.1158/1535-7163.c.6769274
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from APR-246 enhances colorectal cancer sensitivity to radiotherapy

Abstract: <div>Abstract<p>p53 mutation is common and highly related to radiotherapy resistance in rectal cancer. APR-246, as a small molecule, can restore the tumor-suppressor function to mutant p53. As there is currently no existing study on combining APR-246 with radiation in rectal cancer, our objective was to investigate whether APR-246 could enhance the sensitivity of colorectal cancer cells, regardless of their p53 status, to radiation treatment. The combination treatment had synergistic effects on HCT… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In a tumor growth assay, 20 μM APR 246 and 6 Gy both halved the mut xenograft size, whereas the combination brought it down to ≈1/5, but wt cells showed only a 30% APR 246 reduction, and null and mut cells were similar [37]. Interestingly, Venn diagrams of significantly enriched pathways and genes for combined and radiation-alone treatments were also included for wt, mut, and TP53 null cells [110]. APR 246 and PRIMA-1 are therefore very interesting compounds to improve the treatment possibilities of the multitude of LDRR tumors (cf the U1690 SCLC cell survival in Figure 33) that have a mutant TP53 pathway (>50% of all tumors) and therefore otherwise may need ion therapy to counteract their LDRR phenotype property as the treatment response is then generally more independent of the p53 status.…”
Section: Adjuvant Treatmentsmentioning
confidence: 99%
“…In a tumor growth assay, 20 μM APR 246 and 6 Gy both halved the mut xenograft size, whereas the combination brought it down to ≈1/5, but wt cells showed only a 30% APR 246 reduction, and null and mut cells were similar [37]. Interestingly, Venn diagrams of significantly enriched pathways and genes for combined and radiation-alone treatments were also included for wt, mut, and TP53 null cells [110]. APR 246 and PRIMA-1 are therefore very interesting compounds to improve the treatment possibilities of the multitude of LDRR tumors (cf the U1690 SCLC cell survival in Figure 33) that have a mutant TP53 pathway (>50% of all tumors) and therefore otherwise may need ion therapy to counteract their LDRR phenotype property as the treatment response is then generally more independent of the p53 status.…”
Section: Adjuvant Treatmentsmentioning
confidence: 99%
“…In the context of low-LET RT, a recent study indicated that APR-246 is mediating radiosensitization effects through both p53dependent as well as p53-independent manners [42].…”
Section: Introductionmentioning
confidence: 99%